Innovation in Indian Healthcare: Using Health Information Technology to Achieve Health Equity for American Indian and Alaska Native Populations - Carroll, Mark (American Health Information Management Association, 2011)
The US Indian health system utilizes a diverse range of health information technology and innovative tools to enhance health service delivery for American Indians and Alaska Natives. This article provides an overview of efforts and experience using such tools to achieve health equity for American Indian and Alaska Native communities. Specific attention is given to the Indian Health Service Electronic Health Record and to two examples of telehealth innovation.